Coronary and Peripheral Vasomotor Responses to Mental Stress - Muhammad Hammadah (Wiley, 2018)
BackgroundCoronary microvascular dysfunction may contribute to myocardial ischemia during mental stress (MS). However, the role of coronary epicardial and microvascular function in regulating coronary blood flow (CBF) responses during MS remains understudied. We hypothesized that coronary vasomotion during MS is dependent on the coronary microvascular endothelial function and will be reflected in the peripheral microvascular circulation. Methods and ResultsIn 38 patients aged 59±8 years undergoing coronary angiography, endothelium‐dependent and endothelium‐independent coronary epicardial and microvascular responses were measured using intracoronary acetylcholine and nitroprusside, respectively, and after MS induced by mental arithmetic testing. Peripheral microvascular tone during MS was measured using peripheral arterial tonometry (Itamar Inc, Caesarea, Israel) as the ratio of digital pulse wave amplitude compared to rest (peripheral arterial tonometry ratio). MS increased the rate‐pressure product by 22% (±23%) and constricted epicardial coronary arteries by −5.9% (−10.5%, −2.6%) (median [interquartile range]), P=0.001, without changing CBF. Acetylcholine increased CBF by 38.5% (8.1%, 91.3%), P=0.001, without epicardial coronary diameter change (0.1% [−10.9%, 8.2%], P=not significant). The MS‐induced CBF response correlated with endothelium‐dependent CBF changes with acetylcholine (r=0.38, P=0.03) but not with the response to nitroprusside. The peripheral arterial tonometry ratio also correlated with the demand‐adjusted change in CBF during MS (r=−0.60, P=0.004), indicating similarity between the microcirculatory responses to MS in the coronary and peripheral microcirculation. ConclusionsThe coronary microvascular response to MS is determined by endothelium‐dependent, but not endothelium‐independent, coronary microvascular function. Moreover, the coronary microvascular responses to MS are reflected in the peripheral microvascular circulation.